Lisianthus 'UF Savanna' -- Eight Colors of Heat-Tolerant Single-Flowering Cultivars Released by the University of Florida's Lisianthus Breeding Program. - Brent K. Harbaugh; Zhanao Deng (EDIS, 2007)
ENH-1066, a 5-page fact sheet by Brent K. Harbaugh and Zhanao Deng, reports the release of these cultivars appropriate for flowering potted plants, with intermediate height and a spray-type flower display. Published by the UF Department of Environmental Horticulture, February 2007.